2013
DOI: 10.3892/ijmm.2013.1269
|View full text |Cite
|
Sign up to set email alerts
|

Temporal differential effects of proinflammatory cytokines on osteoclastogenesis

Abstract: Bone destruction and inflammation are closely linked. Cytokines play an important role in inflammatory bone destruction by upregulating the receptor activator of nuclear factor-κB (NF-κB) ligand (RANKL). The direct role of cytokines that act in a non-RANKL-dependent manner has yet to be elucidated. The aim of this study was to investigate the direct osteoclastogenic properties of inflammatory cytokines at different time-points of osteoclastogenesis. Mouse bone marrow macrophages were stimulated with the macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 31 publications
0
41
0
1
Order By: Relevance
“…Nevertheless, there are some contradictory studies and reports demonstrating that TNF-α may help and promote osteogenic differentiation. Such discrepancy may be due to the concentration and the differentiation state of the cell type used as well as the exposure time [3,5]. TNF-α may also have cross-talk with many other signaling pathways, such as MAPK, Wnt, and TGF-β/BMP signaling during osteogenic differentiation [2,5,8], which may inhibit the growth, proliferation, and differentiation of osteoblasts and their progenitors [2].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nevertheless, there are some contradictory studies and reports demonstrating that TNF-α may help and promote osteogenic differentiation. Such discrepancy may be due to the concentration and the differentiation state of the cell type used as well as the exposure time [3,5]. TNF-α may also have cross-talk with many other signaling pathways, such as MAPK, Wnt, and TGF-β/BMP signaling during osteogenic differentiation [2,5,8], which may inhibit the growth, proliferation, and differentiation of osteoblasts and their progenitors [2].…”
Section: Introductionmentioning
confidence: 97%
“…Tumor necrosis factor alpha (TNF-α),apro-inflammatory cytokine, plays a pivotal role in inflammation, for example it may activate the nuclear factor kappa-B (NF-κB) signaling which is involved in inflammation and apoptosis of bone cells [1,3,4]. TNF-α is implicated in different inflammatory bone diseases, for example in rheumatoid arthritis and ankylosing spondylitis [2,3,5]. Previous studies have demonstrated that TNF-α may inhibit osteogenesis of mesenchymal stem cells (MSCs) in bone metabolism through down-regulation of runt-related transcription factor-2 (Runx2), osterix (Osx, also known as SP7), and insulin-like growth factor-1 [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive bone resorption by osteoclasts is observed in certain lytic bone diseases, including osteoporosis, hypercalcemia and rheumatoid arthritis, as well as tumor metastases in the bone, periodontitis and Paget's disease (2,3). Patients with lytic bone diseases are at a higher risk of sustaining fractures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AIMP1 enhances the expression of intercellular adhesion molecule-1 (ICAM-1) which plays a critical role in lymphocyte extravasation, inflammation and atherosclerosis [17,18,24]. Furthermore, AIMP1 stimulates the maturation of DCs, which induces the expression of IL-1b, IL-6, and IL-12, cytokines critical for sequential immune activation [16,25,26]. IL-1b and IL-6 are known to stimulate osteoclastogenesis [1].…”
Section: Introductionmentioning
confidence: 98%